1973
DOI: 10.1084/jem.138.3.699
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bacterial Lipopolysaccharides to Show That Two Signals Are Required for the Induction of Antibody Synthesis

Abstract: Evidence is presented that antigen-sensitive cells require two signals for induction. Normally these two signals are delivered to the cell via the recognition of two determinants on the immunogen: the first the receptor on the antigen-sensitive cell, and the second by the cooperating cell system. The special experimental situation described here depends upon the observation that bacterial lipopolysaccharides (LPS) render immunogenic a variety of haptens. When monovalent haptens (TNP-amino acids) are added to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
73
1

Year Published

1973
1973
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 30 publications
2
73
1
Order By: Relevance
“…The mechanism by which the observed antibody response occurred would seem to be best explained by the ability of LPS to bypass the normal T-cell helper function. Such an effect in the antibody production to T-dependent antigens has been previously demonstrated both in vivo or in vitro with antigens such as heterologous erythrocytes (6)(7)(8), haptens (9,10), and with the antigen used in the present studies, namely HGG (11). In this regard, perhaps the most convincing data is that obtained by Watson et al (10), who showed that the spleens of congenitally athymic mice (B cells only) could be induced to form antibody in vitro to a hapten free of any carrier molecule when the culture was supplemented with LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which the observed antibody response occurred would seem to be best explained by the ability of LPS to bypass the normal T-cell helper function. Such an effect in the antibody production to T-dependent antigens has been previously demonstrated both in vivo or in vitro with antigens such as heterologous erythrocytes (6)(7)(8), haptens (9,10), and with the antigen used in the present studies, namely HGG (11). In this regard, perhaps the most convincing data is that obtained by Watson et al (10), who showed that the spleens of congenitally athymic mice (B cells only) could be induced to form antibody in vitro to a hapten free of any carrier molecule when the culture was supplemented with LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms as the cellular level have been investigated extensively but are not yet clear. The enhancing effect (adjuvant effect) of LPS has been thought to be caused by direct activation of B cells by LPS; LPS induces DNA synthesis (15) and polyclonal antibody production by B cells (15,17), and it enhances specific antibody response in circumstances where effects of helper T cells are absent or limited (16,20,28). LPS also prevents induction of immunological tolerance in B cells (12).…”
mentioning
confidence: 99%
“…Its action on antibody response is diphasic, being either enhancing (1, 4,5,14,16,20,21,25,27,28) or suppressive (24). The immune system involving antibody response is composed of several different cell populations (9): B cells, T cells and macrophages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, they show the adjuvant effect, enhancing antibody response to a variety of antigens when administered appropriately [19,25]. Thirdly, they convert tolerogenic or non-immunogenic signals into immunogenic ones [7,16,22,26,28,32] and fourthly, they possess mitogenic activity in transforming bone marrow-derived (B) cells but not T cells [3,27]. Although correlation be- of anti-HGG in response to aggregated HGG alone and upon subsequent injection of LPS they produced higher levels of antibodies but the degrees of increase in serum antibody levels were less than those in C57BL/6 mice ( Fig.…”
mentioning
confidence: 99%